Experimental and numerical investigation on coupled motion characteristics of a tunnel element suspended from a twin-barge. (1st April 2018) - Yang, Can; Weller, Sam D.; Wang, Yong-xue; Ning, De-zhi; Johanning, Lars
Abstract: The coupled motion characteristics of a tunnel element, which is suspended from a twin-barge and moored to the seabed during the installation process, has been investigated using a 1:50 scaled model. Response characteristics are obtained for multiple regular wave conditions and three different immersion depths. Experimental investigation includes studies to identify system properties of individual arrangements (tunnel, twin-barge) and for the coupled tunnel & twin-barge configuration. Investigation of motion characteristics includes i) experimental studies of the tunnel element from a fixed suspension point and barge, ii) experimental studies with and without a mooring arrangement from the tunnel element to the seabed, iii) experimental study of the fully coupled tunnel & twin-barge configuration, and iv) numerical investigation of the fully coupled tunnel & twin-barge configuration using a commercial fully dynamic mooring simulation software (OrcaFlex™). The experimental investigations were carried out in the State Key Laboratory of Coastal and Offshore Engineering at Dalian University of Technology (DUT), using the '6-D Measurement System' (6D-UMS) to obtain six degree of motions for both the tunnel and twin-barge. For the numerical study hydrodynamic properties were obtained from the diffraction/radiation potential code WAMIT for simplified tunnel and twin-barge elements and used to derive fully coupled motion behavior using the time-domain mooring simulation software OrcaFlex™. The results are presented in order to provide insights into the motion characteristics for the different configurations studied. The main findings indicate that the sway and roll motions for the coupled tunnel & twin-barge configuration decrease with increasing wave incidence angle and immersion depths. The use of additional mooring lines to restrain the tunnel element to the seabed played a further role in reducing the motions of the tunnel element, particularly when subjected to large amplitude and long period waves. Highlights: The coupled dynamic response of a moored tunnel element suspended from a twin-barge are experimentally investigated. Response characteristics are obtained for multiple regular wave conditions and three different immersion depths. Additional tunnel mooring system has a limited influence in reducing the motion response of the immersed tunnel element. In sway two excitation modes were observed for the tunnel element, one at low frequency and one at the wave frequency mode. The percentage difference between the tunnel element and twin-barge responses is insignificant in the sway and roll modes. For the heave wave frequency mode the percentage difference decreases with increasing wave height.